1991
DOI: 10.1073/pnas.88.24.11485
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that somatostatin is localized and synthesized in lymphoid organs.

Abstract: Because several peptides ornally found in the pituitary as within the central nervous system have been l i in lymphoid tissues and because somatostatin (soma inrelease-inhibiting hormone, SRIH) can act on cells ofthe immune system, we searched for this peptide in lymphoid organs. We demonstrated that SRIH mRNA exists in lymphoid tissue, albeit in smaller levels than in the perive region of the hypotaus, the brain region that contains the highest level of this mRNA. SRIH mRNA was found in the spleen and thymus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 27 publications
5
50
0
1
Order By: Relevance
“…Indeed, a variety of normal cells, including endocrine and lymphoid cells, that synthesize endogenous somatostatin are known to express somatostatin receptors (28)(29)(30). Furthermore, immunoreactive somatostatin has been found in various types of somatostatin receptor-positive tumor cell lines such as breast cancer cells and colonic tumor cells (31,32) and somatostatin mRNA was detected in a wide variety of neuroendocrine tumors known to express somatostatin receptors (33,34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a variety of normal cells, including endocrine and lymphoid cells, that synthesize endogenous somatostatin are known to express somatostatin receptors (28)(29)(30). Furthermore, immunoreactive somatostatin has been found in various types of somatostatin receptor-positive tumor cell lines such as breast cancer cells and colonic tumor cells (31,32) and somatostatin mRNA was detected in a wide variety of neuroendocrine tumors known to express somatostatin receptors (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…First-strand cDNA synthesis was then carried out with total RNA in 50 mM Tris-HCl buffer (pH 8.3) containing 200 U of Moloney murine leukemia virus reverse transcriptase, 26.5 M oligod(T), 1 mM dNTP, 20 U RNAsin, 10 mM dithiothreitol, 75 mM KCl, 3 mM MgCl 2 in a final volume of 20 l. The sample was incubated for 10 min at 23 Њ C followed by 2 h at 39 Њ C. The RT mixture was then chilled on ice and diluted two-fold with sterile water. PCRs were carried out as described (36) with 1.25 U of Taq polymerase, 1 M specific sense and antisense primers, 250 M of dNTPs, in 10 mM Tris-HCl buffer (pH 9) containing 50 mM KCl, 1.5 mM MgCl 2 , 0.01% Triton X-100 in a final volume of 50 l. After denaturation of the sample at 94 Њ C for 10 min, PCR was carried out on a DNA Thermal Cycler (Techné Laboratories, Princeton) for varying sequential (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) cycles with denaturation at 94 Њ C for 1 min, annealling at 51-62 Њ C for 1 min, and extension at 72 Њ C for 1.5 min. The amplification was terminated by a final extension step at 72 Њ C for 10 min.…”
Section: Reagentsmentioning
confidence: 99%
“…Among lymphatic organs, the thymus from different species, including the human, has been shown to contain the highest amount of SS (7,8,18). Although experimental models in animals have suggested the signi®cant participation of different neuropeptides in the activities of the thymus, the exact role of SS in this context is still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the expressions of neurotrophin-3 (KatohSemba et al 1996), brain-derived neutrotrophic factor (Katoh-Semba et al 1997), vasoactive intestinal peptide (Gomariz et al 1993), and somatostatin (Aguila et al 1991) in minor cell types of these two tissues. Expression of methionine-enkephalin, neuropeptide Y, and substance P were also reported in a similar cell subset of the thymus (Atoji et al 1997).…”
Section: Discussionmentioning
confidence: 99%